Alternative and New Radiopharmaceutical Agents for Lung Cancer - Telo, Silvi; Calderoni, Letizia; Vichi, Sara; Zagni, Federico; Castellucci, Paolo; Fanti, Stefano (Current Radiopharmaceuticals, 2020)
Background: FDG PET/CT imaging has an established role in lung cancer (LC) management. Whilst it is a sensitive technique, FDG PET/CT has a limited specificity in the differentiation between LC and benign conditions and is not capable of defining LC heterogeneity since FDG uptake varies between histotypes. Objective: To get an overview of new radiopharmaceuticals for the study of cancer biology features beyond glucose metabolism in LC. Methods: A comprehensive literature review of PubMed/Medline was performed using a combination of the following keywords: “positron emission tomography”, “lung neoplasms”, “non-FDG”, “radiopharmaceuticals”, “tracers”. Results: Evidences suggest that proliferation markers, such as 18F-Fluorothymidine and 11CMethionine, improve LC staging and are useful in evaluating treatment response and progression free survival. 68Ga-DOTA-peptides are already routinely used in pulmonary neuroendocrine neoplasms (NENs) management and should be firstly performed in suspected NENs. 18F-Fluoromisonidazole and other radiopharmaceuticals show a promising impact on staging, prognosis assessment and therapy response in LC patients, by visualizing hypoxia and perfusion. Radiolabeled RGD-peptides, targeting angiogenesis, may have a role in LC staging, treatment outcome and therapy. PET radiopharmaceuticals tracing a specific oncogene/signal pathway, such as EGFR or ALK, are gaining interest especially for therapeutic implications. Other PET tracers, like 68Ga-PSMA-peptides or radiolabeled FAPIs, need more development in LC, though, they are promising for therapy purposes. Conclusion: To date, the employment of most of the described tracers is limited to the experimental field, however, research development may offer innovative opportunities to improve LC staging, characterization, stratification and response assessment in an era of increased personalized therapy.
Keywords: non-FDG tracers